Educação física, gênero e futebol de meninas em uma escola pública de Lavras-MG: de pouquinho em pouquinho a gente vai conquistando - Andrade, Luciene de Aguiar (2021)
This research aimed to investigate a group of girls from a public school in the city of Lavras- MG who, along with the Physical Education teacher, pleaded and won better spaces and time to practice futsal in a systematic way in that educational space. Acknowledging that futsal is still considered a male sport, this research starts from the understanding of the presence of unequal relationships between boys and girls in the sports universe and sought to know what the experiences and training processes that futsal has made possible for these girls. Some female members of the futsal group and the Physical Education teacher who is also the group’s tutor participated in this research. According to the chosen methodology, online interviews were carried out, synchronous or not, with the girls and the teacher so that we could collect the empirical material. The collected narratives were analyzed on a qualitative basis and through discourse analysis, and it is worth mentioning that they were also anchored by post-critical and post-structuralist theories, mainly studies on gender relations in sport and physical education at school. From the analysis of the empirical material, we concluded that futsal remains a male reserve area and that there were several forms of transgression and resistance structured by girls to dismantle the power relations present in sport, especially in futsal. Finally, we highlight the relevance of a co-educational approach to mitigate gender inequalities present in Physical Education classes and in the sports universe, given that the teacher’s involvement, in one way or another, favored the emergence, permanence and development of the group of girl futsal players. It is hoped that the problematizations of this research corroborate with the discussions about women’s football at school and beyond, in the search for greater scientific investment in the field and political action for equity.